Metode Pendidikan Spiritual Santri: Studi Komparasi di Pondok ‎Pesantren Mansyaul Ulum dan Pondok Pesantren Miftahul Ulum ‎Putri/PPRU IV Ganjaran Gondanglegi Malang - Jamilah, Milatul; Baiquni, Muhammad Masykur (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2023)
This article examines the differences in methods of spiritual education for students between two Islamic boarding schools, namely the Mansyaul Ulum Islamic Boarding School and the Miftahul Ulum Putri/PPRU 4 Ganjaran Gondanglegi Malang Islamic Boarding School. To examine this article, a qualitative comparative study method was used. The data collection process uses observation, interviews and documentation. The findings of this research indicate that the spiritual education methods applied at the Mansyaul Ulum Islamic Boarding School are 1) gathering or congregation which consists of congregational prayer activities, book deliberation, maqom pilgrimage, tahlil reading, and yellow book recitation; 2) humming or Al-Insyad which consists of reading the Prophet's birthday and diba', srakalan, reciting burdah, and reciting Asmaul Husna prayers. Meanwhile, the spiritual education methods applied at the Miftahul Ulum Putri/PPRU IV Islamic Boarding School are 1) the Al-Sahr method (not sleeping at night) which includes congregational evening prayers; 2) the method of gathering or congregation which consists of congregational prayer activities, reading ratibul haddad, reading wirdhul lathif, majlis dalailul khoirot, recitation of the yellow book, as well as recitation of the Al-Qur'an and community pilgrimage; 3) the humming method or Al-Insyad which consists of reading maulid and burdah.